Using connectivity map to identify natural lignan justicidin A as a NF-κB suppressor. (July 2017) - Won, Shen-Jeu; Yen, Cheng-Hsin; Hsieh, Hao-Wen; Chang, Shao-Wei; Lin, Chun-Nan; Huang, Chi-Ying F.; Su, Chun-Li
Highlights: Identify molecular actions of phytochemicals using L1000 and connectivity map. L1000 is to quantify mRNA expressions of 1000 selected landmark genes per sample. Connectivity map contains gene expression signatures from 1309 small compounds. A novel natural lignan justicidin A was revealed to act as a NF-κB suppressor. Justicidin A indeed suppressed NF-κB and induced caspase-independent apoptosis. Abstract: Justicidin A (JA), a natural lignan, was isolated from the whole plant of Justicia procumbens, one of the most popular traditional Chinese medicines in China and Taiwan. Gene expression signatures of JA from human colorectal cancer HT-29 and hepatocellular carcinoma Hep 3B cells were used to query connectivity map. A NF-κB suppressor (15-delta prostaglandin J2) was predicted to display similar molecular action of JA. In JA-treated HT-29 cells, suppression of nuclear NF-κB expression and decrease of NF-κB DNA-binding activity were indeed observed. The classical pathway was involved in JA-induced inhibition of NF-κB, characterized by decreases in phosphorylation of AKT, IκB kinase (IKK)-β/IKK-α, and IκB-α. Furthermore, JA caused significant translocation of apoptosis-inducing factor and endonuclease G, caspase-independent apoptotic signaling molecules, from the mitochondrial to the nuclei. Our data suggest anti-inflammatory and cytotoxic mechanisms of JA, and using gene expression signatures to identify novel molecular actions of phytochemicals is an effective approach.